Impact Lite Dataset - Silvestri, Silvia; Rufino, Mariana C.; Quirós, Carlos F.; Douxchamps, Sabine; Teufel, Nils; Singh, Dhiraj; Mutie, Ianetta; Ndiwa, Nicholas N.; Ndungu, Anthony; Kiplimo, Jasper; Wijk, Mark T. van; Herrero, Mario (2014)
IMPACTlite survey dataset: detailed information about household composition, production systems and activities, land and labour allocatio n, income from on farm and off farm activities, household consumption of food, and asset, with a particular gender lens on control over resources, land ownership and allocation of activities. Standardized detailed survey instrument (IMPACTlite) carried on in 13 benchmark sites across East Africa, West Africa and South Asia.